L’idée en peinture au XVIIe siècle - Dauvois, Daniel (RACAR : Revue d'art canadienne / Canadian Art Review, 2012)
In a letter to Chantelou dated 22 December 1647, Poussin writes of a painting to be executed that he has found its thought, “I mean the conception of the idea, and the work of the mind was complete.” It follows that Poussin’s idea belongs to the theoretical component of painting, namely the composition, and the idea constitutes the represented object aimed at by invention, which converts a historia into a picture and whose procurement provides sufficient satisfaction to an erudite painter like Poussin. Idea is the end or aim of pictorial thought and the regulative means for producing the visible work. Beyond a then perceptible tension between an ideal, indeed a divine Idea, to which Félibien’s idea of the painter comes close in his first Entretien, and an agent or force of conversion of the discursive into the figural, idea belongs henceforth also to the theory of the art of painting, as is witnessed by the titles of works by Fréart or Roger de Piles (Idée de la perfection de la peinture, Idée du peintre parfait): such an idea is thus a regulated presentation of what the painter must do if he wishes to excel. It is no longer conceived or made visible by the painter, but by a kind of enlightened connoisseur, not yet called a critic, but who distances himself sufficiently from the art of painting to teach and to adjudicate good taste. Not only does idea then aid, not in the fabrication of good paintings, but rather in the evaluation of painting, as Roger de Piles underlines at the end of his opuscule introducing the Abrégé de la vie des peintres, but it could well be formative or constitutive of taste itself—a shift by which Idea comes, by the century’s end, to regulate not the production of works, but the judgments passed on them.